Bilateral trade between Thailand and China with gravity model: Evidence from copula-based MS-SUR approach - Petchaluck Boonyakunakorn (2018)
© 2017 Serials Publications Pvt. Ltd. This paper aims to investigate the characteristic factors of bilateral Thailand-China trade from the copula-based Markov Switching Seemingly Unrelated Regression (MS-SUR) model with the gravity model. We estimate the export and import demand equations representing China's demand for Thailand's exports and Thailand's demand for imports from China. The result suggests that the best-fitted model based on both AIC and BIC criteria is both normal distribution for export equation and import equation, and joint distribution by the Frank copula. Based on the findings, GDP's of both China and Thailand are the main factors driving Thailand's import from China in market upper regime. In contrast, China's GDP, FDI's China, and ACFTA decrease Thailand's import in downward upper regime. The filtered probabilities of the upper regime of the trade market shows that the trade between Thailand and China operates mostly in the upper regime rather than in the downturn regime.